Liability risks in shareholders’ engagement via electronic communication and social media - Aiman Nariman, Mohd Sulaiman; Hingun, Mohsin (Emerald Publishing Limited, 2020)
This paper aims to examine the potential liability of companies and their board members arising from the use of digital technology and social media as communication and engagement tools with investors and shareholders. Design/methodology/approach – The research relies on a qualitative study using legal analysis of corporate and capital market laws as well as the outcome of legal proceedings and regulatory actions to ascertain conduct that could expose companies and boards to liability risks. Findings – Social media characteristics expose unwary directors and companies to potential liability for oppressive conduct, selective disclosure or misleading statements. Research limitations/implications – This paper informs boards and companies of the types of conduct that could expose companies and boards to liability when social media is relied on to communicate with shareholders and investors. Originality/value – The paper contributes to the literature on social media, capital market and corporate communication by presenting the legal perspective concerning reliance on social media as shareholders’ engagement and corporate communication tool.